Biomechanical changes with increased speed in elite middle-distance runners - Hanley, B.; Cooke, M.; Gallagher, L.; Oh, Y. K.; Parelkar, P.; Thomas, A.; Tucker, C. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Distance runners train at different speeds to enhance their physiological and biomechanical capabilities to ensure that their aerobic and anaerobic energy systems are optimised for the demands of racing. The kinematic, kinetic, spatiotemporal, and global stiffness changes that occur as an athlete increases speed are not well understood in well-trained middle-distance runners. The aim of this study was to analyse the biomechanical responses of middle-distance athletes to increases in treadmill speed. METHODS: Thirteen male athletes (1.79 ± 0.07 m, 66.7 ± 6.1 kg, 22.3 ± 3.2 y) and two female athletes (stature: 1.69 ± 0.01 m, mass: 55.7 ± 0.4 kg, 30.9 ± 2.6 y) participated. Their mean World Athletics points for personal best performances were 1114 (± 73). Each athlete ran on a Gaitway 3D instrumented treadmill (1000 Hz) during an incremental test at 12, 16, 20 and 24 km/h. Data were collected during the second half of each 1-min stage. Two Fastec T5 high-speed cameras (200 Hz) were placed to the sides of the treadmill to record each side of the body separately, and the starting times were synchronised with the treadmill`s data collection period. Ground reaction force (GRF) and spatiotemporal data were measured using the treadmill software; lower limb joint angles were measured using the high-speed videos in SIMI Motion; and global stiffness characteristics were calculated using peak vertical GRF via the methods of Morin et al. (JAB, 2005, 21(2), 167-180). RESULTS: Both step length and cadence increased at each faster running speed (from 1.24 m and 2.70 Hz at 12 km/h to 2.01 m and 3.32 Hz at 24 km/h). Ground contact time decreased during each stage (0.229, 0.194, 0.168 and 0.147 s, respectively), but flight time only increased until 20 km/h (0.143, 0.160 and 0.163 s), with lower values at 24 km/h (0.155 s). Duty factor decreased during each stage (0.308, 0.274, 0.254 and 0.244, respectively) although leg stiffness was consistent throughout testing (11.4, 11.4, 11.4 and 11.6 N/mm, respectively). Vertical push-off rate increased consistently during each stage (31.6, 41.4, 51.2 and 59.9 BW/s, respectively). The main changes that occurred in joint angles and positions at initial contact were an increase in thigh angle (21, 25, 28 and 29°, respectively), shank angle (3, 5, 7 and 8°, respectively) and hip-ankle horizontal distance (0.18, 0.22, 0.25 and 0.27 m, respectively). CONCLUSION: It was unsurprising that athletes increased step length and cadence with faster treadmill belt speeds, although the increase in cadence from 20 to 24 km/h was the only one that arose from both shorter contact and flight times. The lack of reliance on increased flight time, and the very small increases in joint angles and positions from 20 to 24 km/h, show that there is an anthropometric limit on achieving faster speeds, which require greater force production during the push-off phase. Athletes should thus note the need for appropriate strength and conditioning within their training regimens.